Effect of processing method on platycodin D content in Platycodon grandiflorum roots - Kwon, Jaeyoung; Lee, H.; Kim, N.; Lee, J.-H.; Woo, M.H.; Kim, J.; Kim, Y.S.; Lee, D. (Pharmaceutical Society of Korea, 2017)
Platycodon grandiflorum root is a traditional medicine and food material rich in triterpenoid saponins. Its major constituent, platycodin D (PD), is known to have various pharmacological properties, but processing methods may influence the PD content. In this study, a fully validated HPLC？ELSD method was developed for the quantification of PD in various states of 73 P. grandiflorum root samples from East Asia, and it exhibited a marked variation of the content. Furthermore, the effects of processing procedures such as peeling and drying temperature on the PD content were investigated using UPLC？ELSD analysis, and as a result, a significant influence of processing methods such as peeling and heating of samples on the content was confirmed. Specifically, unpeeled samples that were dried at 40？°C showed the greatest PD content. The obtained results could facilitate the reliable standardization of P. grandiflorum for precise authentication and efficacious applications. ？ 2017, The Pharmaceutical Society of Korea.